The effects of a bike active video game on players' physical activity and motivation - Denis Pasco; Cédric Roure; Gilles Kermarrec; Zachary Pope; Zan Gao (Elsevier, 2017)
Background: Players may not acquire adequate levels of moderate-to-vigorous physical activity (MVPA) when playing commercial video games. This study's goal was to evaluate the effects of an exercise bike video game played by using a mobile application-based exergame that was designed exclusively to promote participants' MVPA, with additional attention paid to this game's ability to promote greater situational interest. Methods: An experimental design was used with 163 students (aged 20.31 ± 1.30, 18-26 years, 61.3% male), all of whom were randomly allocated into an experimental group and a control group. Physical activity (PA) levels were assessed with ActiGraph GT3X+ (ActiGraph Inc., Fort Walton Beach, FL, USA) accelerometers. The situational interest scale was used to evaluate students' situational interest in both groups. Multivariate analysis of variance was conducted to examine the differences between sedentary behavior, PA levels, and situational interest between groups. Regression analyses were also used, with the purpose being to evaluate the strength of the relationship between PA and situational interest. Results: Results revealed that the experimental group had higher degrees of sedentary behavior, light PA, total interest, instant enjoyment, exploration intention, attention demand, novelty, and challenge, whereas the control group received higher scores for MVPA (control 95.01% vs. experimental group 89.94%). Regression analysis indicated that instant enjoyment (β = 0.49, p < 0.01), exploration intention (β = 0.18, p < 0.05), and attention demand (β = 0.17, p < 0.05) were positive predictors for total interest, explaining 43% of its variance. Conclusion: A newly designed mobile application-based exergame played via an exercise bike may enhance situational interest and provide a decent level of PA for players.